PEMANFAATAN ARANG AKTIF SERBUK GERGAJI KAYU BANGKIRAI (Shorea lavefolia Endert) SEBAGAI ADSORBEN PELUMAS (OLI) BEKAS - Youlanda, Desy; Sitorus, Saibun; Yusuf, Bohari (Jurusan Kimia FMIPA UNMUL, 2022)
The use of bangkirai wood sawdust as adsorbent for used lubricant (oil) adsorption has been carried out. The purpose of this research is to find out how activated charcoal from bangkirai wood sawdust (Shorea Lavefolia Endert) can be used as a lubricating adsorbent (oil) seen from the testing and characterization of activated charcoal. The process of making bangkirai wood sawdust activated charcoal 0 is through a carbonization process at 500 C for 15 minutes and an activation process is carried out in activated charcoal by soaking using 25% H3PO4 solution for 24 hours. Determination of the quality of activated charcoal is carried out by testing the moisture content, ash content and iodine absorption capacity. The results obtained were the water content of activated charcoal H3PO4 25% which was 1,0590%, the ash content of activated charcoal H3PO4 25% was 0,0998% and the absorption capacity of activated charcoal H3PO4 activated charcoal 25% was 375,3253 mg/g. The optimum conditions for the adsorption of used lubricant (oil) were using activated charcoal adsorbent bangkirai wood sawdust, namely the mass of 1,5 grams and the contact time of 30 minutes. Keywords: Adsorption, Oil, Activated Charcoal, sawdust, bangkirai wood